2016
DOI: 10.1080/14647273.2016.1243817
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of concurrent administration of mifepristone and misoprostol for termination of pregnancy

Abstract: In this prospective randomized parallel group study, subjects with a pregnancy of less than 63 d were randomized to receive either (i) 200 mg oral mifepristone plus 400 μg misoprostol per vaginally concurrently (group A); (ii) or the administration of misoprostol after 48 h (group B). Transvaginal sonography was performed on the 14th day of misoprostol administration to confirm complete abortion. The primary outcome was to compare the rates of complete abortion in two groups. Secondary outcomes were to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Eight studies assessed different time intervals between mifepristone and misoprostol dosing in the combined regimen. These include comparisons between < 8 h vs. > 24 h [11,12], 24 h vs. 48 h [13,32,40], concurrent administration vs. 24 h [25,38] and < 8 h vs. 48 h [37] ( Table 2).…”
Section: 2comparison Of Dosing Intervals Between Mifepristone and mentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies assessed different time intervals between mifepristone and misoprostol dosing in the combined regimen. These include comparisons between < 8 h vs. > 24 h [11,12], 24 h vs. 48 h [13,32,40], concurrent administration vs. 24 h [25,38] and < 8 h vs. 48 h [37] ( Table 2).…”
Section: 2comparison Of Dosing Intervals Between Mifepristone and mentioning
confidence: 99%
“…There may be little to no difference in rates of successful abortion between concurrent administration of misoprostol and a 24-h interval (RR 1.01 CI 95% 0.84-1.21, very low certainty of evidence) [25,38]. There was no significant difference between 24-h and 48-h interval in terms of ongoing pregnancy and successful abortion [13,32,40].…”
Section: 2comparison Of Dosing Intervals Between Mifepristone and mentioning
confidence: 99%
“…In two of the studies it was unclear whether allocation concealment was adequate,3 4 with the same concern being an issue for the randomisation method in one of those studies 4. Finally, one of the studies was at high risk of selective reporting bias with a number of stated outcomes not reported 4. All three studies were at low risk of attrition bias for all reported outcomes apart from patient satisfaction in the Creinin et al study, which was at high risk of attrition bias with data missing for 10% of the population in each intervention group 2…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies assessed different time intervals between mifepristone and misoprostol dosing in the combined regimen. These include comparisons between < 8 hours vs. > 24 hours [8,9], 24 hours vs. 48 hours [10,21,22], concurrent administration vs. 24 hours [23,24] and < 8 hours vs. 48 hours [25] (Table 2).…”
Section: Comparison Of Dosing Intervals Between Mifepristone and Misomentioning
confidence: 99%
“…There may be little to no difference in rates of successful abortion between concurrent administration of misoprostol and a 24-hour interval (RR 1.01 CI 95% 0.84-1.21, very low certainty of evidence) [23,24]. There was no signi cant difference between 24-hour and 48-hour interval in terms of ongoing pregnancy and successful abortion [10,21,22].…”
Section: Comparison Of Dosing Intervals Between Mifepristone and Misomentioning
confidence: 99%